An investigation on the cytotoxicity and caspase-mediated apoptotic effect of biologically synthesized gold nanoparticles using Cardiospermum halicacabum on AGS gastric carcinoma cells - Li C (Dove Medical Press, 2019)
Chunfeng Li,1 Yimin Wang,1 Hongfeng Zhang,1 Man Li,2 Ziyu Zhu,1 Yingwei Xue1 1Gastrointestinal Surgical Ward, Harbin Medical University Cancer Hospital, Harbin, Heilongjiang 150081, China; 2Department of Endoscopy, Harbin Medical University Cancer Hospital, Harbin, Heilongjiang 150081, China Background: Gastric cancer is the fourth most common cancer and second leading cause of cancer death worldwide. Cardiospermum halicacabum is used to treat nerve disorders, stiffness, rheumatism, ear ache, snake bite, and so on. Methods: In this study, the reaction parameters were optimized to control the size of the nanoparticle, which was confirmed by transmission electron microscopy. Various characterization techniques such as selected area diffraction pattern, UV-visible spectroscopy, energy-dispersive X-ray analysis, dynamic light scattering, Fourier-transform infrared spectroscopy, and atomic force microscopy were employed to analyze the synthesized AuNPs obtained from C. halicacabum (CH-AuNP) against gastric carcinoma cell line. Results: The cytotoxic effect of CH-AuNP against AGS, SNU-5, and SNU-16 cell lines was detected by MTT assay. The induction of apoptosis by CH-AuNP in AGS was analyzed by double staining technique using TUNEL and DAPI staining assays. Further to confirm the molecular mechanism exhibited by CH-AuNP to induce apoptosis, the intracellular ROS level was assessed and immunoblotting was performed to assess the apoptotic signaling molecules that often deregulated in cancerous condition. Conclusion: The results clearly prove that CH-AuNP increases ROS and induces apoptosis in AGS, suggesting that CH-AuNP may be an effective anticancer drug with no side effects to treat gastric cancer. Keywords: gastric cancer, gold nanoparticle Cardiospermum halicacabum, apoptosis, MMP, ROS